2018
DOI: 10.1111/apa.14390
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparities in preterm neonatal outcomes

Abstract: The male disadvantage in preterm outcomes is likely multifactorial with hormonal, genetic and immunological differences likely playing key roles. Gender is an important variable in preterm outcome and should be considered when designing clinical and experimental research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
84
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 61 publications
14
84
3
1
Order By: Relevance
“…Sex is known to have a significant bearing on neonatal outcomes with male preterm infants experiencing more adverse outcomes than females 33 , and yet we saw very few significant differences in immune parameters between male and female infants. The few immune differences that were identified may, therefore, be functionally relevant.…”
Section: Discussionmentioning
confidence: 86%
“…Sex is known to have a significant bearing on neonatal outcomes with male preterm infants experiencing more adverse outcomes than females 33 , and yet we saw very few significant differences in immune parameters between male and female infants. The few immune differences that were identified may, therefore, be functionally relevant.…”
Section: Discussionmentioning
confidence: 86%
“…This nding is in agreement with nding of a study in Australia. It reported that risk of neonatal sepsis was found increase three times more in male neonates as compared to female neonates (30). Male sex is associated with a higher risk of neurological, pulmonary, cardiovascular and infectious morbidities as well as overall mortality when compared to female infants of similar preterm gestation (29).…”
Section: Discussionmentioning
confidence: 99%
“…Important differences in the immune response between male and female preterm neonates have also been noted (31). However, the etiology of sex-speci c differences in disease remains relatively undetermined and is likely multifactorial, with genetic, immunological and hormonal in uences playing key roles (30).…”
Section: Discussionmentioning
confidence: 99%
“…Increased rates of respiratory disorders among boys are partly due to their delayed lung maturation. 27 Sex hormones have been shown to impact fetal lung development with androgens negatively and estrogens positively, influencing surfactant production. 27 -29 However, to our knowledge, there have been no studies in which the authors examined whether changes in morbidities, as reported in recent studies, 1, 2, 4 have affected male and female infants differently.…”
Section: Discussionmentioning
confidence: 99%